POWER RELATIONS IN ACADEMIC DISCOURSE: A CRITICAL DISCOURSE ANALYSIS OF LECTURER-STUDENT INTERROGATION DURING UNDERGRADUATE THESIS DEFENSE SESSIONS (RELASI KUASA DALAM WACANA AKADEMIK: STUDI WACANA KRITIS INTEROGASI DOSEN-MAHASISWA PADA UJIAN SKRIPSI PROGRAM SARJANA) - Sultan Sultan; Muhammad Rapi; Muhammad Bahly Basri; Suardi Suardi (Universitas PGRI Sumatera Barat, 2022)
Due to the unequal positions of the participants, academic interactions that occur during undergraduate thesis defense sessions in universities are a social arena that allows the emergence of power relations. This study sought to elucidate the forms of interrogation employed by lecturers in academic discourse during undergraduate thesis defense sessions. This study employed a qualitative approach with a critical discourse analysis design. Data were collected through recording, observation, and interviews and then evaluated using a critical discourse analysis framework. The results showed that lecturers used various forms of questions in academic interactions, including closed-ended questions, open-ended questions, and task-oriented questions. These questions reflect the unequal relationship between lecturers and students. Lecturers have the authority to control and dominate academic interactions in undergraduate thesis defenses.